Self‐Organization of Polyurethane Pre‐Polymers as Studied by Self‐Consistent Field Theory. Issue 1 (2nd September 2015) - Li, Feng; Tuinier, Remco; van Casteren, Ilse; Tennebroek, Ronald; Overbeek, Ad; A. M. Leermakers, Frans
Abstract : Using self‐consistent field (SCF) theory, we studied the self‐assembly characteristics of polyurethane pre‐polymer dispersions in aqueous solutions. With a molecularly detailed model implementing the Scheutjens–Fleer discretization scheme, it is shown how the stability, equilibrium size, and internal structure of the (swollen) micelles in polyurethane (PU) dispersions depend on the chemical structure and the molecular composition of the charged pre‐polymer mixtures. The stability region of these micelles is found to increase when acid groups become deprotonated and when the ionic strength is lowered. Insight into the physical–chemical behavior of PU pre‐polymer dispersions is important for the subsequent process of film formation from the PU dispersions for the final coating properties. Abstract : Using self‐consistent field (SCF) theory with a molecularly detailed model, the authors study the self‐assembly of polyurethane pre‐polymer dispersions in aqueous solutions. Insight into the physical–chemical behavior of PU pre‐polymer dispersions is obtained. Details like radial volume fraction distribution of six representative PU pre‐polymers and water on a single swollen micelle are shown in this paper.